POG08 Novel mitochondrial tRNA mutation associated with migraine, pigmentary retinopathy, leukoencephalopathy and sensorineural deafness. Issue 11 (22nd October 2010) - Panicker, J; Taylor, R W; Blakely, E L; Wilson, M
Abstract : A 34-year-old lady was referred to the headache clinic. She had a long history of migraines starting as a teenager with bilateral throbbing headaches associated with photophobia, phonophobia and nausea with no other focal neurological symptoms. She had bilateral, mild sensorineural deafness which had started as a child, but without a specific diagnosis. There was no other significant past medical history, but there was a strong family history of migraine in her mother, two brothers and a sister. Neurological examination was normal except for florid pigmentary changes in both retinae and bilateral sensorineural deafness. Brain MRI showed extensive periventricular white matter changes confined to the white matter with callosal sparing. Screening for common CADASIL mutations had proven negative. She underwent a muscle biopsy of the left tibialis anterior muscle which showed mild myopathic changes and occasional ragged-red fibres, but histochemistry revealed a high proportion of cyclooxygenase-deficient fibres (60% of the total biopsy), indicative of a primary mitochondrial DNA (mtDNA) aetiology. Common mtDNA mutations were excluded, but sequencing of the entire mitochondrial genome revealed a novel sequence variant m.16023G>A in the tRNAPro ( MTTP ) gene which was present at high levels of heteroplasmy. The m.16023G>A variant affects an evolutionary conserved residue of the tRNAPro molecule and is the likely explanation for the clinical presentation and muscle biopsy changes.